Genetic variations associated with non-contact muscle injuries in sport: A systematic review - Lim, T.; Santiago, C.; Pareja-Galeano, H.; Iturriaga, T.; Sosa-Pedreschi, A.; Fuku, N.; Pérez-Ruiz, M.; Yvert, T. (Scandinavian Journal of Medicine & Science in Sports, 2021)
Introduction: Non-contact muscle injuries (NCMI) account for a large proportion of sport injuries, affecting athletes` performance and career, team results and financial aspects. Recently, genetic factors have been attributed a role in the susceptibility of an athlete to sustain NCMI. However, data in this field are only just starting to emerge. Objectives: To review available knowledge of genetic variations associated with sport-related NCMI. Methods: The databases Pubmed, Scopus, and Web of Science were searched for relevant articles published until February 2021. The records selected for review were original articles published in peer-reviewed journals describing studies that have examined NCMI-related genetic variations in adult subjects (17-60 years) practicing any sport. The data extracted from the studies identified were as follows: general information, and data on genetic polymorphisms and NCMI risk, incidence and recovery time and/or severity. Results: Seventeen studies examining 47 genes and 59 polymorphisms were finally included. 29 polymorphisms affecting 25 genes were found significantly associated with NCMI risk, incidence, recovery time, and/or severity. These genes pertain to three functional categories: (i) muscle fiber structural/contractile properties, (ii) muscle repair and regeneration, or (iii) muscle fiber external matrix composition and maintenance. Conclusion: Our review confirmed the important role of genetics in NCMI. Some gene variants have practical implications such as differences of several weeks in recovery time detected between genotypes. Knowledge in this field is still in its early stages. Future studies need to examine a wider diversity of sports and standardize their methods and outcome measures.